Secreted aspartic proteases of Candida albicans, Candida tropicalis, Candida parapsilosis and Candida lusitaniae. Inhibition with peptidomimetic inhibitors - Pichová, I; Pavlícková, L; Dostál, J; Dolejsí, E; Hrusková-Heidingsfeldová, O; Weber, J; Ruml, T; Soucek, M (European journal of biochemistry, 2001)
The frequency of Candida infections has increased in recent years and it has been accompanied by a significant rise in morbidity and mortality. The secretion of aspartic proteases by Candida spp. was demonstrated to be one of the virulence determinants. Candida albicans is classified as the major human pathogen in the genus Candida. However, other species of this genus have been found to cause an increasing number of candidiases. We isolated secreted aspartic proteases (Saps) of C. albicans (Sap2p), C. tropicalis (Sapt1p), C. parapsilosis (Sapp1p), and C. lusitaniae (Saplp) from culture media. All the isolated proteases were N-terminally sequenced. Their specific proteolytic activities and sensitivity to series of peptidomimetic inhibitors modified in the type of scissile bond replacement as well as in the N- and C-termini were analyzed. The most divergent substrate specificity was observed for the Sap of C. tropicalis. The specificity of Sap of C. lusitaniae is most closely related to that of Sap of C. parapsilosis. We designed and prepared an inhibitor containing phenylstatine isoster that was equipotent towards all four proteases within the range of 10-10-10-9 M. The HIV-1 protease inhibitors ritonavir, saquinavir, indinavir, and nelfinavir were also tested for the inhibition of four Saps. Only ritonavir and saquinavir inhibited Sap2p, Sapt1p, Sapp1p, and Saplp in micromolar concentrations.
Keywords: techniky in vitro; Kinetics; substrátová specifita; kinetika; Candida albicans; inhibitory proteas; Pepstatins; Sequence Homology, Amino Acid; lidé; Molecular Sequence Data; Aspartic Acid Endopeptidases; sekvence aminokyselin; Humans; Protease Inhibitors; Candida; sekvenční homologie aminokyselin; Substrate Specificity; aspartátové endopeptidasy; Amino Acid Sequence; In Vitro Techniques; molekulární sekvence - údaje; pepstatiny